Efficacy and safety of ginger in osteoarthritis patients: a meta-analysis of randomized placebo-controlled trials. Issue 1 (January 2015) - Bartels, E.M.; Folmer, V.N.; Bliddal, H.; Altman, R.D.; Juhl, C.; Tarp, S.; Zhang, W.; Christensen, R.
Summary: The aim of this study was to assess the clinical efficacy and safety of oral ginger for symptomatic treatment of osteoarthritis (OA) by carrying out a systematic literature search followed by meta-analyses on selected studies. Inclusion criteria were randomized controlled trials (RCTs) comparing oral ginger treatment with placebo in OA patients aged >18 years. Outcomes were reduction in pain and reduction in disability. Harm was assessed as withdrawals due to adverse events. The efficacy effect size was estimated using Hedges' standardized mean difference (SMD), and safety by risk ratio (RR). Standard random-effects meta-analysis was used, and inconsistency was evaluated by the I-squared index ( I 2 ). Out of 122 retrieved references, 117 were discarded, leaving five trials (593 patients) for meta-analyses. The majority reported relevant randomization procedures and blinding, but an inadequate intention-to-treat (ITT) analysis. Following ginger intake, a statistically significant pain reduction SMD = −0.30 ([95% CI: [(−0.50, −0.09)], P  = 0.005]) with a low degree of inconsistency among trials (I 2 = 27%), and a statistically significant reduction in disability SMD = −0.22 ([95% CI: ([−0.39, −0.04)]; P = 0.01; I 2 = 0%]) were seen, both in favor of ginger. Patients given ginger were more than twice as likely to discontinue treatment compared to placebo ([RR = 2.33; 95% CI: (1.04, 5.22)]; P = 0.04; I 2 = 0%]). Ginger was modestly efficacious and reasonably safe for treatment of OA. We judged the evidence to be of moderate quality, based on the small number of participants and inadequate ITT populations. Prospero: CRD42011001777.